Academic Factors Influencing Non-English Students’ Willingness to Communicate in English Classroom (A study in Nursing Students) - Mustaqimah Muh Tang; Muhammad Jufrianto; Sahril Nur (Universitas Muhammadiyah Enrekang, 2022)
Abstract: In EFL classrooms, one of the primary goals of the teaching and learning process is to increase students' willingness to communicate (WTC). In higher education institutions in Indonesia, this study aims to identify variables that may affect students' WTC in EFL classes, specifically for nursing students. The quantitative research method was used in this research. In this study, questionnaire data were collected from 38 nursing students at Fatima Parepare (9 males, or 76.3%, and 29 females, or 23.7%). Descriptive statistics using percentage representations were used to analyse the study's data. The results of the present study thus demonstrate that speaking up in group discussions is one of the WTC's influencing elements for EFL students. Other findings from the study include: 1) the participant said that always eager to speak practice the speaking skills; 2) they find that discussions in group are the engaging activities in the English classes; 3) they are excited to speak if the discussion starting with number of critical questions; 4) the students find it easy to communicate and discuss in group.